Executives’ role, characteristics and strategic choice in the digital age - Islam, Sigma (2025)
Digital technologies have transformed the business landscapes by changing the nature of products, services, business models and operations, which are influencing how organisations can create value through their corporate strategies and emphasising the need for digital strategy.